Dampak Special 301 terhadap Industri Rekaman Indonesia - Hendra Tanu Atmadja (Fakultas Hukum Universitas Islam Indonesia, 2003)
The United States'strong commitment to global protection of intellectual property rights is rooted in its goal to preserve or regain the competitiveness and dominance of United States exports. In recent years, the United States has been experiencing significant and growing trade imbalances with its trading partners. The development of the Section301 provisions in the Omnibus Trade and Competitiveness Act of 1988 (